ANALISIS MODEL PENGAWASAN BERBASIS KINERJA DALAM PENJAMINAN MUTU PENDIDIKAN TERHADAP PENILAIAN KINERJA GURU DI SEKOLAH - Rismayani, Risha; Mija Indra Putra; Syahril; Irsyad; Novriyanti Achyar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the performance-based supervision model in educational quality assurance concerning the evaluation of teacher performance in schools. The approach used is qualitative with a literature review method, which involves examining various scientific sources such as journals, books, and relevant educational policy documents. The findings indicate that performancebased supervision can enhance the objectivity, accountability, and effectiveness of teacher performance evaluation when supported by clear indicators, standardized instruments, and continuous follow-up. However, its implementation still faces several challenges, including limited supervisory competencies, a weak evaluation culture, and suboptimal utilization of data. Therefore, it is necessary to strengthen an integrated supervision system within the framework of educational quality assurance.